2019
DOI: 10.1093/jisesa/iey132
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Novel Attract-and-Kill Strategy forDrosophila suzukii(Diptera: Drosophilidae) Management

Abstract: The invasion of the spotted wing drosophila, Drosophila suzukii Matsumura, across the Americas and Europe has led to increased insecticide applications to protect fruit crops. This insecticide usage conflicts with integrated pest management programs, as well as harvest, export, and pollination services in the affected crops. A novel management tool was assessed against D. suzukii that may mitigate these conflicts. HOOK SWD, an attract-and-kill (A&K) formulation applied as a sprayable bait, was evaluated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 28 publications
(32 reference statements)
1
25
0
Order By: Relevance
“…For example, the leaves of pepper trees and their extracts have been used to repel house flies ( Musca domestica ) in Ethiopia (Abdel-Sattar et al 2010), and peppermint oils have been shown to be repellent towards D. suzukii in a laboratory setting (Renkema et al 2016). However additional, economically viable strategies to combat D. suzukii still need to be identified, as most research has focused on attractive odors for monitoring or bait and kill strategies for population control (Klick et al 2019; Landolt et al 2012;).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the leaves of pepper trees and their extracts have been used to repel house flies ( Musca domestica ) in Ethiopia (Abdel-Sattar et al 2010), and peppermint oils have been shown to be repellent towards D. suzukii in a laboratory setting (Renkema et al 2016). However additional, economically viable strategies to combat D. suzukii still need to be identified, as most research has focused on attractive odors for monitoring or bait and kill strategies for population control (Klick et al 2019; Landolt et al 2012;).…”
Section: Introductionmentioning
confidence: 99%
“…15,16,19,20,22 Attractand-kill technology using red sticky spheres impregnated with an insecticide appears effective at killing 100% of D. suzukii in confined greenhouse conditions within 24 h, and significantly wileyonlinelibrary.com/journal/ps reducing D. suzukii infestation in the field. 54,55 Similarly, HOOK SWD, a sprayable attracticidal bait comprised of an insecticide, sugar, and pink food coloring, significantly lowers infestation in the field compared to plots treated with an insecticide alone. 56 A push-pull system that uses these or similar attracticidal visual, olfactory, and gustatory tools along the perimeter of planting, in combination with octenol or other putative repellents (D. Cha, unpublished data) throughout the interior, may provide growers with an invaluable method for reducing infestation in a more targeted, ecologically sustainable manner compared to current calendar-based insecticide applications.…”
Section: Discussionmentioning
confidence: 99%
“…10,36,57 These data also highlight the importance of developing and employing multiple methods of pest control during a given season, as no one technology can sustainably manage pest populations throughout the growing/fruiting window. While semiochemical disruption methods are beneficial, other measures, including targeted chemical insecticide applications, physical exclusion using netting 55 and/or enclosed high tunnels, 58 or cultural control measures including clean harvest, field sanitation, and wild host removal 13,41 may be required to achieve effective control.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, a multi-modal device that combined an attractive kairomone, phagostimulant, and visual attractant resulted in highly effective AK of the apple maggot fly, Rhagoletis pomonella (Walsh) (Diptera: Tephritidae) ( Wright et al 2012 ). The same has been accomplished with a multi modal SPLAT matrix formulation to control spotted wing drosophila, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), that relies on semiochemical and visual attractants to lure and phagostimulant to incite the fly to manipulate and consume the insecticide-laced bait ( Klick et al 2019 ). Finally, another possibility for improvement might be in the choice of insecticide incorporated into the AK.…”
Section: Discussionmentioning
confidence: 99%